La pliometría y la efectividad en el lanzamiento del tiro de tres puntos. - Camacho Rivera, Juan Francisco (2023)
The main purpose of this research study was to focus on Plyometric which is a type of training that involves the rapid contraction and stretching of muscles to improve explosive strength and power. In the context of three-point shooting in basketball, plyometrics can be an effective tool to improve shooting accuracy and distance. The present research aims to demonstrate the impact of the application of plyometrics on the effectiveness of the three-point shot in basketball players through the application of a training plan of plyometric exercises for basketball players at the learning level, in a population of 15 pre-adolescents between 14 and 15 years of age, during 4 weeks. A pretest was applied at the beginning of the research to determine the level at which the population is and at the end of it a post-test, where it was determined that there are significant differences in the performance of the group studied, differences that are focused on the increase in the percentage of effectiveness in three-point shots.